Cash in the City : The Case of Port-au-Prince - D'Aoust, Olivia; Gunneman, Julius; Patel, Karishma V.; Tassot, Caroline (World Bank, Washington, DC, 2022)
Following the 2010 devastating earthquake and subsequent cholera epidemic, Port-au-Prince’s residents have been increasingly affected by food insecurity, socio-economic unrest including periods of complete lock-down, and gang violence. In light of the insecurity which limits the possibilities to collect the necessary information to target the vulnerable residents of Port-au-Prince, this paper aims at providing meaningful evidence to inform the remote targeting and delivery of a potential social assistance program. Putting together household and geospatial data, we compute a composite vulnerability indicator for the metropolitan area, offering a first snapshot of inequality and vulnerability within the city, and discuss the results’ implications for social protection programming.